Emotion dysregulation in borderline personality disorder: a fronto-limbic imbalance? - Sicorello, Maurizio; Schmahl, Christian (Current opinion in psychology, 2021)
Borderline personality disorder is most consistently characterized as a disorder of the experience and regulation of emotions. Neuropathological models have predominantly explained these clinical traits with an imbalance between prefrontal regulatory and limbic emotion generating structures. Here, we review the current evidential state of the fronto-limbic imbalance hypothesis of borderline personality disorder, based on task-related functional magnetic resonance imaging research. In turn, we discuss challenges to the notion that (1) amygdala hyperreactivity underlies emotional hyperreactivity and deficits in (2) prefrontal activity or (3) fronto-limbic connectivity underly emotion regulation deficits. We offer several suggestions to improve consolidation and interpretation of research in this area.